Multivariable evaluation of maternal hemodynamic profile in pregnancy complicated by fetal growth restriction: prospective study. (11th November 2019) - Di Martino, D. D.; Ferrazzi, E.; Garbin, M.; Fusè, F.; Izzo, T.; Duvekot, J.; Farina, A.
ABSTRACT: Objective: To evaluate the association between fetal growth restriction (FGR) and maternal hemodynamic parameters using multivariable analysis, adjusting for major confounding factors, such as hypertensive disorders of pregnancy (pre‐eclampsia and gestational hypertension). Methods: A prospective cohort study was conducted between January 2013 and April 2016. Two cohorts of patients were recruited, between 24 and 39 weeks of gestation, in a high‐risk outpatient setting. These cohorts comprised 49 appropriate‐for‐gestational‐age singleton fetuses and 93 that were FGR (abdominal circumference (AC) at recruitment in the second half of pregnancy ≤ 10 th percentile with a previous normal AC at 20–22 weeks). Maternal echocardiography was performed at the time of enrolment and included hemodynamic parameters of systolic and diastolic function and cardiac remodeling indices. Data were analyzed using a multivariable generalized linear model to estimate the association of FGR with maternal hemodynamic parameters after adjusting for significant confounding factors. Results: In the multivariable analysis, after adjustment for hypertensive disorders of pregnancy and smoking, FGR was associated with a 14% increase in maternal total vascular resistance, 16% reduction in cardiac output, 13% reduction in left ventricular mass and 11% reduction in heart rate; similar results were observed for the corresponding indexed parameters. Hypertensive disorders of pregnancy in the absence of FGR were associated with a 25% increase in total vascular resistance, 16% increase in left ventricular mass and 14% reduction in diastolic function; similar results were observed for the corresponding indexed parameters. Conclusion: FGR is significantly and independently associated with several maternal hemodynamic parameters, even after adjustment for major confounding factors, such as hypertensive disorders of pregnancy. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.